The agri-food sector in Romania: An analysis of the resources-utilization correlation in the post-accession period - Elena Carmen Bucur; Sorinel Ionel Bucur (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
As important part of national economy, the agri-food sector had oscillating evolutions in the post-accession period, mainly generated by the need to get in line with the EU requirements. The analysis of the resources-utilizations ratio, from the point of view of production account, reveals significant modifications, as regards both the direct relations between the different subsectors of national economy and the relation between the overall sector and the rest of national economy. Based on data processing from the input-output table from national accounts, the present approach tries to make a diagnosis of the agri-food economy resources utilization in relation to other branches of the economy.
Keywords: 330; resources; utilizations; national accounts; agri-food sector